2022
DOI: 10.3390/molecules27165323
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Severe COVID-19 on Plasma Antioxidants

Abstract: Several studies suggested the association of COVID-19 with systemic oxidative stress, in particular with lipid peroxidation and vascular stress. Therefore, this study aimed to evaluate the antioxidant signaling in the plasma of eighty-eight patients upon admission to the Clinical Hospital Dubrava in Zagreb, of which twenty-two died within a week, while the other recovered. The differences between the deceased and the survivors were found, especially in the reduction of superoxide dismutases (SOD-1 and SOD-2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…However, given the observed results of the Nrf2 antioxidant response in the lung biopsies of COVID-19 patients, which indicate the suppression of genes associated with the Nrf2 antioxidant response, and in vitro experiments that have shown that the expression of Nrf2 inducible proteins is also reduced, it is likely that the suppression of this metabolic pathway occurs in COVID-19 patients [41]. These data are in agreement of the decreased SOD1 and SOD2 activities observed in current study, reflecting also decrease of the SOD levels recently revealed in the plasma of COVID-19 patients [43]. In contrast, the inverse granulocyte response to COVID-19 with respect to HO-1 may be a specific gene response of that protein or the type of cell whose antioxidant response was analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…However, given the observed results of the Nrf2 antioxidant response in the lung biopsies of COVID-19 patients, which indicate the suppression of genes associated with the Nrf2 antioxidant response, and in vitro experiments that have shown that the expression of Nrf2 inducible proteins is also reduced, it is likely that the suppression of this metabolic pathway occurs in COVID-19 patients [41]. These data are in agreement of the decreased SOD1 and SOD2 activities observed in current study, reflecting also decrease of the SOD levels recently revealed in the plasma of COVID-19 patients [43]. In contrast, the inverse granulocyte response to COVID-19 with respect to HO-1 may be a specific gene response of that protein or the type of cell whose antioxidant response was analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…In another study, to determine the relationship between COVID-19 and oxidative stress (vascular stress and lipid peroxidation), the authors demonstrated that there was a reduction in antioxidant capacity, and thus, the patients were unable to counteract oxidative modifications [ 37 , 38 ]. Moreover, our results are consistent with previous studies indicating that oxidative stress markers are significantly elevated in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This research is critical because it helps to understand the interventions that can be incorporated to reduce adverse outcomes, such as the potential of developing other adverse conditions during high viral load, such as in the case of COVID-19. For instance, Žarković suggested how to respond to patients with SARS-CoV-2 by administering antioxidants such as lipophilic agents that can help to counter the spread of the virus [ 38 ]. Furthermore, Chavarría et al established that antioxidant therapy can help to reduce the severity of conditions such as COVID-19 because it improves the survival rates of critical outcomes such as sequential organ failure assessment (SOFA) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few important biological functions related to selected features in severity prediction with reasonable p-value are floor plate formation, alpha-2B adrenergic receptor binding [35] , thymus development [21] , [48] , positive regulation of histone modification and chromatin organization [4] , [77] , [96] , nephron tubule epithelial cell differentiation [112] , HMG box domain binding [40] , [41] , [97] , platelet formation and morphogenesis [10] , [64] , [83] , positive regulation/regulation of memory T cell activation [45] , [66] , interleukin-4-dependent isotype switching to IgE isotypes, response to nitrogen dioxide [119] , [47] , [69] , axon part and terminus, neuron projection terminus, synapse, mesonephric tubule formation, metanephric mesenchyme development [107] , syntaxin-1 binding [81] , stereocilia ankle link complex, regulation of actin phosphorylation, aminophospholipid transport [9] , positive regulation of long term synaptic depression [13] , [73] , nuclear RNA export factor complex [46] , motor neuron apoptotic process, positive regulation of norepinephrine secretion [61] , cellular response to lipid hydroperoxide [117] , [60] , modified amino acid binding, PCSK9-AnxA2 complex, glutathione binding [103] , [28] , [53] , oligopeptide binding [3] , [58] , metalloendopeptidase inhibitor activity, glutathione derivative metabolic [28] and biosynthetic process [36] , mesonephric tubule formation, zymogen granule, nephron tubule epithelial cell differentiation and negative regulation of regulatory T cell differentiation [105] .…”
Section: Study On the Selected Featuresmentioning
confidence: 99%